Peran Sosial Media Marketing dan E-Commerce dalam Meningkatkan Daya Saing dan Jangkauan Pasar UMKM di Desa Kedungjambe - Hakim Mahdi Zakariya; Maharani Ikaningtyas (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
This study aims to enhance the competitiveness and market reach of Micro, Small, and Medium Enterprises (MSMEs) in Kedungjambe Village through the optimization of social media marketing and e-commerce platforms. The primary challenge faced by MSMEs is limited consumer visibility due to ineffective promotional and marketing strategies. The proposed solution includes training on digital marketing strategies utilizing social media platforms like WhatsApp Business for interactive communication with customers and leveraging the features of the Shopee e-commerce platform to expand market reach. MSME participants were trained to create engaging promotional content, utilize WhatsApp Business broadcast features to foster customer engagement, and effectively manage online stores on Shopee, including crafting informative product descriptions, managing inventory, and analyzing sales performance. A simulation of digital marketing through Shopee was conducted to provide hands-on experience for the business owners. The results of the program demonstrated a significant improvement in MSME competitiveness, brand awareness, customer engagement through social media, and sales volume on Shopee.